FRACTAL STRUCTURE OF TITANIUM NITRITE DEPOSITED ON STAINLESS STEEL SUBSTRATE - Yu.V. Brylkin (Физико-химические аспекты изучения кластеров, наноструктур и наноматериалов, 2014)
On the basis of images obtained using scanning tunneling microscope, it was shown that the fractal dimension can be considered as some universal surface characteristic of the titanium nitrite, deposited on stainless steel.